Zika virus like particles elicit protective antibodies in mice. - Mauricio A Salvo; Brock Kingstad-Bakke; Cristhian Salas-Quinchucua; Erwin Camacho; Jorge E Osorio (PLoS Neglected Tropical Diseases, 2018)
Mosquito-borne Zika virus (ZIKV) typically causes a mild and self-limiting illness known as Zika fever. Since its recent emergence in 2014 in the American continent, ZIKV infection during pregnancy has been closely associated with a wide range of congenital abnormalities. To date, no vaccines or antivirals are publicly available. We developed Zika virus-like particles (VLPs) and evaluated their immunogenicity and protective efficacy in mouse models. ZIKV VLPs (ZIKVLPs) formulated with alum were injected into 6-8-week-old interferon deficient AG129 mice as well as wild type BALB/c mice. Control mice received PBS/alum. Animals were challenged with 200 PFU (>1000 AG129 LD50s) of ZIKV strain H/PF/2013. All vaccinated mice survived with no morbidity or weight loss while control animals either died at 9 days post challenge (AG129) or had increased viremia (BALB/c). Neutralizing antibodies were observed in all ZIKVLP vaccinated mice. The role of neutralizing antibodies in protecting mice was demonstrated by passive transfer. Our findings demonstrate the protective efficacy of the ZIKVLP vaccine and highlight the important role that neutralizing antibodies play in protection against ZIKV infection.